Community Empowerment in Rural Areas Through the Cultivation and Production of Traditional Medicines Based on Medicinal Plants in Batu Tanjung Village, Talawi, Sawahlunto City - Dillasamola, Dwisari; Putri, Biomechy Oktomalio; Noverial; Fadil, Muhammad Syukri; Marwan; Hasibuan, Ahmad Daniel; Pratiwi, Eghinna Elsa; Hafsah, Nur; Oktafani, Reni; Fadhilla, Naylatul; Oktaviani, Dilla; Hendriansah; Putri, Popy Dwi; Amanda, Amelia; Muhadzid, Fayyadh Atsil; Dewi, Lativa Andam; Thoriq, Muhammad; Andrisyah, Fauzi; Azizi, Adni Salsabil; Yazid, Muhammad; Amalina, Azka; Naufal, Muhammad; Hanisa, Najma Syakina; Ramadhani, Nasywa Anjani; Mufadhdhal, Muhammad Asad (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2025)
The utilization of Family Medicinal Plants (TOGA) is a strategic effort to enhance community health self-reliance, reduce dependence on synthetic drugs, and preserve local biodiversity. In Nagari Batu Tanjung, Talawi District, Sawahlunto City, the potential for TOGA is high due to favorable geography and extensive backyard land. However, its use remains limited because of low herbal literacy, minimal organic cultivation skills, and the absence of a properly managed communal garden. This community service program aimed to empower residents through education, direct practice, and guidance in cultivating and processing medicinal plants. Activities included awareness sessions on TOGA’s benefits, land preparation, planting of herbal seeds (ginger, turmeric, cardamom, sungkai, Java turmeric, aloe vera), and the establishment of a model TOGA garden. Based on pre- and post-test results from 40 participants, knowledge and cultivation skills improved significantly—from 40% to 95% of participants understanding proper TOGA cultivation. Active collaboration among residents, village officials, and students ensured the program’s success. Through Q&A sessions and hands-on practice, the community gained practical skills suited to local conditions. The established TOGA garden now serves as a learning medium, a health-supporting initiative, and a foundation for developing herbal products that promote sustainable economic empowerment.